Neue Lösung für ein altes Problem : Aktuelle Entwicklungen bei oralen Kontrastmitteln - Fork, Thomas; Adnerhill, Ingvar; Böök, Olof; Casal-Dujat, Lucia; Leander, Peter; Makitan, Mladen ; 0009-0007-3054-813X; Marsal, Jan ; 0000-0003-4808-0014 (Radiologie (Heidelberg, Germany), 2023)
BACKGROUND: Several radiological societies in Europe have so far spoken out in favor of MRI of the small intestine over CT, since MRI is said to provide more detailed image information. Due to the limited availability of MRI machines, long waiting times arise for many patients who clinically require small bowel imaging. OBJECTIVES: These circumstances guided our search for an improved CT technique that would provide scans that mimic the image impression of T1 sequence in MRI, i.e. with IV contrast-enhanced intestinal wall versus low/no signal lumen. MATERIAL AND METHODS: The oral use of fat or oil is poorly tolerated by patients, as is the placement of a naso-duodenal tube for air insufflation. We have now succeeded in creating a foamy drink with 44% air content, which is kept stable by protein together with buffers, and can be easily administered orally. CT with the Lumentin® beverage as bowel filling agent has been tested on healthy adult volunteers; oncology patients; and Crohn's disease patients who, for comparison, also underwent MRI of the small bowel with conventional oral contrast. RESULTS: The results so far with Lumentin® show a very good distribution throughout the entire small intestine with good lumen distension, images with strongly enhanced contrast of the intestinal mucosa, and lesions that are detected at the same or increased frequency as compared with MRI. Side effects were few and mild, and overall fewer than with commonly used oral agents. Lumentin's foamy consistency was unfamiliar to a few patients, but it wasn't difficult to drink. CONCLUSIONS: The new and innovative luminal HU-negative contrast agent Lumentin® improves the diagnostic CT image quality. In addition, Lumentin® experimental MRI tests have provided promising results, which are currently leading to further clinical MRI studies.
© 2023. The Author(s), under exclusive licence to Springer Medizin Verlag GmbH, ein Teil von Springer Nature.
Keywords: Adult; Humans; Contrast Media; Crohn Disease/diagnostic imaging; Intestine, Small/diagnostic imaging; Intestines; Radiography